(untitled) (Journal of Shaheed Suhrawardy Medical College, 2022)
Objectives: Maternal death was analyzed in Shaheed Suhrawardy Medical College hospital to improve the quality of maternal health care. Methods: In this cross -sectional study, each case was reviewed individually and factors responsible for maternal death were identified and noted. Results: During the study period January 2019 to December 2019 total 16 maternal death recorded among 3410 deliveries. 68% deceased mother were less than 30 years of age. Parity shows 37.50% multipara. 75% deceased mother was delivered by caesarean section, 6% was vaginal delivery and 12.5% mother died undelivered. Regarding time interval 25% of death occurred within 24 hours of admission to hospital. The main causes of death were severe preeclampsia- eclampsia (31.25%), PPH (12.5%), septicemia (12.5%), DIC (12.5%). Some factors were identified and among them lack of proper ANC, delayed admission to hospital, delayed blood transfusion were related. Conclusion: Substantial number of maternal death occurred at or <30 years of age. Preeclampsia-eclampsia, hemorrhage, septicemia were identified as the major cause of maternal death. J Shaheed Suhrawardy Med Coll 2020; 12(2): 63-66